Normal and oblique drop impact of yield stress fluids with thixotropic effects - Oishi, Cassio M. [UNESP]; Thompson, Roney L.; Martins, Fernando P. [UNESP] (Cambridge Univ Press, 2019)
Normal and oblique drop impact on a solid surface is numerically analysed for yield stress fluids. A rich diversity of results are generated as a consequence of the exploration of the inertial, elastic, plastic and thixotropic features of the process, as well as the inclination of the solid surface. We show that drops of more thixotropic fluids have a higher tendency to bounce in the normal impact, and to roll or to bounce in the case of an oblique drop impact. Concerning elasticity, we found a critical value for the elastic Ohnesorge number above which no bouncing takes place. Experimental findings such as the fact that the stored energy due to the elasticity of the fluid drop plays a role similar to the stored energy of an interfacial nature in inelastic fluid drops are corroborated in the present study.
Keywords: drops; non-Newtonian flows; interfacial flows (free surface)